Writing and teaching the past to transform the present: the Marxist influence on the reflection on the meaning of history in the "long sixties" in Chile - Ortiz Figueroa, Matías (Meridional. Revista Chilena de Estudios Latinoamericanos, 2023)
The article analyzes the Marxist influence over Chilean historiography, as well as in the national proposals for history teaching at school level during the 1960's decade. Specifically, it is addressed the meaning that was given by intellectuals, academics, and students to the development of historical research and teaching. Thus, beyond the matters referred to methods and conceptual drifts, the articule aims to capture the function that was given to the social role of the historical discipline through a ideological platform, highlighting the political, social and democratizing meaning that the study of past immanently charged for the referred actors. The article proposes that, unlike conservative history and the ways of teaching history arose from it, the proposals that are being analyzed have in the center of its questioning the historical present, as well as the political conjunctures and the phenomenon of the inequalities, redefining the usefulness of the study of the past from an ethical and political perspective, with a socialist and Latin American projection, interrupting the linear and progressive historical time that characterized the “traditional” history in Chile in the 1960's.